Retinal microvascular network attenuation in Alzheimer's disease. Issue 2 (15th May 2015) - Williams, Michael A.; McGowan, Amy J.; Cardwell, Chris R.; Cheung, Carol Y.; Craig, David; Passmore, Peter; Silvestri, Giuliana; Maxwell, Alexander P.; McKay, Gareth J.
Abstract: Introduction: Cerebral small‐vessel disease has been implicated in the development of Alzheimer's disease (AD). The retinal microvasculature enables the noninvasive visualization and evaluation of the systemic microcirculation. We evaluated retinal microvascular parameters in a case‐control study of AD patients and cognitively normal controls. Methods: Retinal images were computationally analyzed and quantitative retinal parameters (caliber, fractal dimension, tortuosity, and bifurcation) measured. Regression models were used to compute odds ratios (OR) and confidence intervals (CI) for AD with adjustment for confounders. Results: Retinal images were available in 213 AD participants and 294 cognitively normal controls. Persons with lower venular fractal dimension (OR per standard deviation [SD] increase, 0.77 [CI: 0.62–0.97]) and lower arteriolar tortuosity (OR per SD increase, 0.78 [CI: 0.63–0.97]) were more likely to have AD after appropriate adjustment. Discussion: Patients with AD have a sparser retinal microvascular network and retinal microvascular variation may represent similar pathophysiological events within the cerebral microvasculature of patients with AD.